Monitoring of IL-1β and MCP-1 Levels in Diabetic Patients with Foot Ulcer Infections: Pemantauan Kadar IL-1β dan MCP-1 pada Pasien Diabetes dengan Infeksi Luka Kaki - Mays Ibrahim Al-Wakeel (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Diabetic foot ulcers (DFUs) are among the most severe complications of diabetes mellitus, often complicated by persistent infections that delay healing and increase morbidity. Specific Background: Chronic DFUs are associated with exaggerated inflammatory responses, where cytokines such as interleukin-1β (IL-1β) and monocyte chemoattractant protein-1 (MCP-1) play pivotal roles in tissue damage and impaired recovery. Knowledge Gap: Despite evidence linking cytokines to inflammation, their diagnostic and prognostic utility in monitoring infection severity and bacterial involvement in DFUs remains insufficiently explored. Aims: This study evaluated serum IL-1β and MCP-1 levels in diabetic patients with infected foot ulcers, examining associations with ulcer severity, gender, and microbial isolates. Results: Compared with healthy controls, diabetic patients exhibited significantly elevated IL-1β and MCP-1 levels, which strongly correlated with each other and increased with Wagner ulcer stage. Staphylococcus aureus was the predominant bacterial isolate, followed by E. coli and P. aeruginosa. Gender-specific differences were observed, with males showing higher cytokine concentrations, while correlations were stronger among females. Novelty: The study demonstrates a clear link between pro-inflammatory cytokines and ulcer severity, highlighting their potential as biomarkers for disease monitoring. Implications: Incorporating IL-1β and MCP-1 assessments into clinical practice may improve early diagnosis, guide therapeutic strategies, and support personalized management of diabetic foot infections.Highlight : IL-1β and MCP-1 increase with ulcer severity as reliable biomarkers. Staphylococcus aureus dominates bacterial isolates in diabetic foot ulcers. Persistent inflammation delays proper wound healing. Keywords : Diabetic Foot Ulcer, IL-1β, MCP-1, Inflammatory Cytokines, Wound Healing